THE SPECIFIC CHARACTER OF PEDAGOGICAL HIGHER EDUCATION IN THE CONDITIONS OF PEDAGOGICAL INSTITUTES REORGANIZATION - Alexander N. Novikov; Maria S. Novikova (Высшее образование в России, 2022)
The specificity of pedagogical higher education lies first of all in the organization of the learning process in the pedagogical institute, and in the specificity of students’ and teachers’ environment; the interaction “teacher – student”; research and education results; teachers’ status; students’ mentality; reflection. In the condition of pedagogical university reorganization, the main task is to preserve the established traditions expressing this particular specificity.